2015
DOI: 10.1007/s00394-015-1005-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory potential of diet and mortality among women in the Swedish Mammography Cohort

Abstract: These results indicate that a pro-inflammatory diet, as indicated by higher DII score, was associated with all-cause and digestive-tract cancer mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 90 publications
4
59
1
Order By: Relevance
“…In line with our findings, in a cohort of US women, the DII was associated with all-cause, cancer, and CVD mortality (30). In another cohort including Swedish women, the DII was associated with all-cause and digestive tract cancer mortality (31). To our knowledge, no other prospective study has previously tested for the association between the DII and mortality, and none had tested this relation in men.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In line with our findings, in a cohort of US women, the DII was associated with all-cause, cancer, and CVD mortality (30). In another cohort including Swedish women, the DII was associated with all-cause and digestive tract cancer mortality (31). To our knowledge, no other prospective study has previously tested for the association between the DII and mortality, and none had tested this relation in men.…”
Section: Discussionsupporting
confidence: 71%
“…Although several studies have been published regarding the associations between the DII and incidence of chronic diseases (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), only 2 studies, restricted to women, have investigated the relation between the pro-and anti-inflammatory potential of the diet measured with the DII and mortality (30,31), and none has studied how this association is modulated by antioxidant supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 shows five studies studying the association between the DII score and all-cause mortality [37,38,39,40,41]. In all studies except one, a higher risk of all-cause death was found among those participants with the highest pro-inflammatory values of the DII score.…”
Section: Mortality and The DII Scorementioning
confidence: 99%
“…Finally, the Swedish Mammography Cohort including a large sample size ( n = 33,747) found a direct association of the DII score with all-cause mortality as well as with CVD mortality (HR = 1.35; 95% CI: 1.01–1.81) when comparing extreme quintiles [41]. However, no significant association was found for cancer mortality or digestive-cancer mortality.…”
Section: Mortality and The DII Scorementioning
confidence: 99%
“…For the updated version, several studies have found associations between DII score and CRP, in adults and seniors [26], and IL-6, tumour necrosis factor-alpha (TNF-α) and another score of combined inflammatory biomarker in postmenopausal women [27]. The DII score has been used in several studies to predict mortality [28,29], survival [30], and diseases, especially cancer [30,31], but also obesity [32], cardiovascular disease [33] and metabolic syndrome [32,34].…”
Section: Introductionmentioning
confidence: 99%